Exports diversification as a key point of Сhina’s trade strategy - Natallia Shalupayeva (Hryhorii Skovoroda University in Pereiaslav, 2021)
Nowadays, economic diversification remains a key challenge for most developing countries. The world trading system is developing from universal liberalization to increased protectionism which imposes additional difficulties in countries’ exports development and puts export diversification at the heart of a strategy for economic diversification. China's foreign trade is also in a critical period of rapid development and transformation at present. China is building a new pattern of integration into the world economic system, but its economic transformation is not smooth and faces problems. Taking into account China’s high reliance on exports, one of the most important threat to China’s economic development – the susceptibility to fluctuations in global economy – is largely due to a low level of Chinese exports diversification. In order to achieve a more sustainable long-term economic growth and hedge against the impact of external shocks China needs to diversify its exports markets, range of exported products and trade methods. Purpose. The purpose of the article is the research of practical aspects of exports diversification in China, identification of features and problems of China’s exports product and market diversification, diversification of trade methods and high-tech products exports diversification. Methodology. The methodological basis of the study is presented by the theories of foreign trade and industrial policy, as well as by the researches realized in the field of exports diversification. The information basis of the study are the databases of UNCTAD, WTO and National Bureau of Statistics of China. General scientific methods, systematic approach, economic-statistical methods are used in the research. Findings. An analysis of China’s exports diversification was realized in the article, including revealing of features and problems of China’s exports product and market diversification, diversification of trade methods and high-tech products exports diversification, as well as identification of some driving effects of China’s exports diversification on its economic development and substantiation of the significance to improve its export diversification strategy in order to reduce economic risks and promote the sustainable development of foreign trade.